Lesion of the ventral or dorsal hippocampus in the rat delays puberty, follicular growth and secretion of sex steroid hormones - Castillo, Estrella del Mar; Quiróz, Ubaldo; Milflores, Lorena; Reyes, Rosalina; Flores, Gonzalo (Frontiers in Endocrinology, 2025)
IntroductionThe hypothalamus-pituitary-gonad axis is controlled by gonadotropins and by a direct neural pathway to the gonads. New evidence suggests the existence of neural connection from the hippocampus to the hypothalamus that can regulate its function. It could be a new control on the well-regulated hormonal and neural connection to the gonads and hence in reproduction. The objective of this study was to analyze the effects of independent lesion of the dorsal or ventral hippocampus in the female rat on the onset of puberty, follicular growth and serum concentration of sex steroid and gonadotropins.MethodsPrepubertal female rats of the CII-ZV strain, 21 days old, were used. Ventral (VH-L) or dorsal (DH-L) hippocampus lesions by the administration of ibotenic acid were performed using stereotaxic surgery. Controls were sham-operated (VH-Sham and DH- Sham), a fifth group was used as absolute control. At 30 days of age all groups underwent novel object recognition tests (NORT).ResultsData from memory using NORT showed a decrease both in short- and long-term memory in the animals in the VH- L and DH-L groups compared to their respective sham-operated controls and the absolute control group. Similarly, injured rats presented delayed vaginal opening and in first vaginal estrus, a decrease in the number of healthy ovarian follicles and an increase in follicular atresia. The ventral or dorsal hippocampus lesions also caused a significant decrease in the secretion of estradiol and progesterone, an increased plasma testosterone. Only DH-L group showed a significant decrease in serum FSH concentrations compared to their respective control groups.DiscussionThese results show for the first time that the hippocampus participates in a stimulatory manner, that could overcome the gonadotropic control by acting by a neural connection to the gonads giving a novel integrative mechanism between learning processes with neuroendocrine mechanism regulating the ovary function.